P5 Model Approach in Alcohol Use Disorders: A Narrative Review of Deaddiction through Ayurveda Perspective - Karishma Pauriyal; Annusuiya Gohil; Nidhi Sharma; Kamal Kumar; Mahesh K. Vyas (Journal of Ayurveda, 2025)
Background: Ayurveda has long recognized the harmful effects of excessive alcohol consumption, known as Madatyaya. P5 model provides a holistic approach to alcohol abuse treatment. Ayurvedic management of alcohol use disorders (AUD) involves detoxification (Shodhana), modifications in diet and lifestyle (Ahara and Vihara), and psychological interventions such as Sattvavajaya Chikitsa, which focuses on cognitive restructuring and mindfulness techniques. Objective: The objective is to assess the applicability and effectiveness of the P5 Model (Predictive, Personalized, Preventive, Participatory, and Psycho-cognitive) in the management and treatment of AUD from an Ayurvedic perspective. Data Source: The references relevant to the above concepts were searched from PubMed, SCOPUS, and Web of Science databases. The relevant portion of Ayurveda is collated from the classical texts. Review Methods: Summarizing and critically analyzing existing literature on an AUD and P5 model without strict inclusion/exclusion criteria. Results: The principles of the P5 model are mentioned extensively in Ayurveda and can be applied in the management of AUD. By analyzing an individual’s physical and mental status through the lens of Ayurveda, early intervention and personalized treatment can be provided. Treatment is tailored to each person’s unique Prakriti, Dosha imbalances, and lifestyle factors. Ayurveda also addresses the psychological and emotional aspects of AUD through therapies such as Sattvavajaya Chikitsa, cognitive restructuring, and mindfulness practices. Encouraging patients to engage in the treatment actively enhances their ability to adopt healthier habits and actively participate in their recovery. Conclusion: By combining the P5 model with Ayurvedic principles, a comprehensive approach to treating AUD is created, tackling not only the physical symptoms but also the psychological, emotional, and social aspects. Ayurveda’s personalized care, tailored to an individual’s constitution and lifestyle, fosters long-term emotional and cognitive healing. With additional research, this model could enhance traditional addiction treatments, offering a more balanced and long-lasting approach to recovery.